Menggali Transformasi Kehidupan Jemaat: Pendekatan Kecerdasan Spiritual dalma Konteks 2 Korintus 5:17 - Nugroho, Binuko Edi; Purwonugroho, Daniel Pesah (Sekolah Tinggi Agama Kristen Diaspora Wamena, 2024)
Change is an inevitable part of human life. Life transformation is necessary for every individual to face changes and not be influenced by their negative impacts. From a Christian perspective, life transformation is essential for Christian congregations. Life transformation from a Christian perspective must have the right trigger. That trigger is spiritual intelligence that is based on the Bible. In the Bible, the life transformation of believers is described in 2 Corinthians 5:17. The application of spiritual intelligence in the lives of Christian congregations aims to make the character of Christ increasingly evident. With the transformation of life that occurs, Christian congregations can be wiser in using the existing technology to glorify God. By using descriptive qualitative methods, it can be concluded that the life transformation of Christian congregations can occur when spiritual intelligence based on 2 Corinthians 5:17 can be applied in the lives of Christian congregations. 2 Corinthians 5:17 explains the meaning of life transformation as a result of the redemption of Jesus Christ. Building spiritual intelligence correctly according to the truth of the Bible in 2 Corinthians 5:17 will bring Christian congregations to experience positive life transformation.AbstrakPerubahan adalah hal yang pasti terjadi di dalam kehidupan manusia. Transformasi kehidupan diperlukan manusia dalam menghadapi perubahan secara positif. Dalam perspektif Kristen, transformasi kehidupan sangatlah penting dan memerlukan pertolongan firman Tuhan sehingga perubahan yang dihasilkan fondasional dalam mengembangkan kecerdasan spiritual yang sesuai dengan ajaran Alkitab. 2 Korintus 5:17 merupakan salah satu konsep transformasi yang mendasar di dalam Alkitab. Paulus mendorong jemaat untuk menginternalisasi penggilan untuk menjadi ciptaan baru dimana integrasi kehidupan dan karakter Kristus merupakan fondasi di dalamnya. Dengan metode kualitatif deskriptif penelitian ini akan mendekati konsep transformasi kehidupan tersebut secara mangkus untuk menolong umat berdialektika secara kontekstual dan kita sebagai para pembaca pada masa kini dapat menarik pelbagai simpul penalaran serta penerapan bagi kehidupan umat pada masa kini. Makna transformasi di dalam 2 Korintus 5:17 dijelaskan sebagai hasil dari penebusan Yesus Kristus. Pembangunan kecerdasan spiritual dengan benar sesuai dengan kebenaran Alkitab dalam ayat 2 Korintus 5:17 akan membawa jemaat Kristen mengalami transformasi kehidupan yang positif.